EFEKTIVITAS COGNITIVE BEHAVIORAL THERAPY (CBT) DALAM MENGURANGI PERILAKU BULLYING - Millatul Hoiroh; Ade Irma Noviyanti; Dewi Masyitoh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to examine the effectiveness of Cognitive Behavioral Therapy (CBT) group counseling in reducing bullying behavior among students at MTs Darul Ulum As-Surur. Bullying remains a persistent problem in Indonesian schools, including religious-based institutions such as madrasah, despite their emphasis on moral education. This study used a quantitative approach with a quasi-experimental nonequivalent control group design, involving 20 eighth-grade students divided into an experimental group (n=10) that received six sessions of CBT-based group counseling and a control group (n=10) that received regular guidance and counseling services. Data were collected using a 24-item bullying behavior questionnaire covering four dimensions: physical, verbal, relational/social, and cyberbullying, which was proven valid (r-count > r-table = 0.422) and reliable (Cronbach's Alpha = 0.792). Data were analyzed using Paired Sample and Independent Sample t-Tests with the help of IBM SPSS Statistics 26. Results showed a significant decrease in bullying scores in the experimental group (pretest M=81.60 to posttest M=40.60; t=22.532; Sig.=0.002<0.05), while the control group showed no significant change (M=79.10 to M=76.80; t=3.214; Sig.=0.111>0.05). The Independent Sample t-Test confirmed a significant difference between the two groups' posttest scores (t=-20.307; df=18; Sig.=0.002<0.05; mean difference=-36.20). These findings indicate that CBT-based group counseling is effective in reducing bullying behavior among madrasah students and may serve as an evidence-based intervention model for school counselors.